TRANSIT : an astrological understanding of the quarter-life crisis - Saw, Li Ying (2019)
Humankind has always looked towards the heavens with wonder, charting maps of the stars in the search for meaning, knowledge and omens. Although the role and reputation of astrology has gone through countless revisions across multiple cultures and eras, the ancient discipline of astrology still remains relevant, controversial, and surprisingly commonplace in this generation ruled by scientific knowledge and rational thought.TRANSIT aims to deconstruct the experience of a quarter-life crisis — a transitory period characterised by uncertainty and doubt “during which individuals relentlessly question their future and how it will follow the events of the past” (Robbins & Wilner, 2008) — through the symbolic language of astrology.